2021
DOI: 10.1590/1806-9282.20210720
|View full text |Cite
|
Sign up to set email alerts
|

Association between thrombocytopenia and platelet profile with morbidity/mortality of severe and non-severe COVID-19 patients

Abstract: OBJECTIVE: Coronavirus disease 2019 (COVID-19) is a novel infectious viral disease that can be associated with changes in platelet counts. Thrombocytopenia is a risk factor for increased mortality and morbidity among these patients. In this study, we aimed to measure the platelet count of COVID-19 patients and find the association with morbidity and mortality after following up. METHODS:This study was conducted on 1,320 confirmed COVID-19 patients who were admitted to the Ayatollah Taleghani and Shohada Tajris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The admission platelet in our study showed no significant difference between both the severe and non-severe groups. The results of our study were in accordance with the study by Khave et al (2021), but in their study, after seven days since the day of admission, there was a tendency to increase the platelet count in the non-severe group compared to the severe group.…”
Section: Resultssupporting
confidence: 92%
“…The admission platelet in our study showed no significant difference between both the severe and non-severe groups. The results of our study were in accordance with the study by Khave et al (2021), but in their study, after seven days since the day of admission, there was a tendency to increase the platelet count in the non-severe group compared to the severe group.…”
Section: Resultssupporting
confidence: 92%
“…As fibrinogen and VWF are engaged in platelet degranulation 44,45 , we hypothesize that the observed decreased levels of proteins from the platelet degranulation pathway in samples from COVID-19 convalescents (Figure 4, cluster A) may be due to low platelet counts resulting from platelet consumption during COVID-19 infection. This hypothesis is supported by studies that suggest a 5% to 42% exhaustion in platelet counts for several months post infection (immune thrombocytopenia) [46][47][48][49] amongst survivors of both severe and non-severe COVID-19 patients [50][51][52][53] . While low platelet counts can occur any time during the acute phase of COVID-19, it has been frequently observed after clinical recovery 54 , e.g.…”
Section: Discussionmentioning
confidence: 78%
“…Common hematological abnormalities in patients infected with SARS-CoV-2 include changes in the number of platelets, white blood cells, Hb, coagulation/fibrinolytic changes and lymphopenia [ 51 ]. Low lymphocytes, low platelets, and clotting problems are the most common hematological disorders [ 52 , 53 , 54 ]. Understanding the hematological characteristics of patients with COVID-19 may help with early triage and prediction of disease severity [ 47 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low lymphocytes, low platelets, and clotting problems are the most common hematological disorders [ 52 , 53 , 54 ]. Understanding the hematological characteristics of patients with COVID-19 may help with early triage and prediction of disease severity [ 47 , 52 , 53 ]. In this study, there were no significant differences between the two groups regarding the mean values of Hb or leukocytes.…”
Section: Discussionmentioning
confidence: 99%